Contextualization of Lean Office for Administrative Process Optimization in Morocco: Critical Analysis and Conceptual Framework - SRHIR , Abdelhak; HOUSSAINI , Abdellah; MAMAD , Mohamed (Revue Internationale des Sciences de Gestion, 2025)
This article explores the relevance and necessity of contextualizing the application of Lean Office for optimizing administrative processes in Morocco. Drawing on a systematic review of international literature (Larsson & Ratnayake, 2021; Elias, 2023), we examine the fundamental concepts of Lean Office (Womack & Jones, 2003; Liker, 2004) and its deployment experiences. A significant lack of theoretical and empirical research specifically dedicated to the Moroccan context is highlighted (Ait Abdelmalek & Houfaidi, 2018; Benhrimida & Dekkaki, 2020), a context characterized by distinct organizational, institutional, and sociocultural specificities (Radnor & Osborne, 2013; Oikaoui & El Oualidi, 2020; Taibi & Benabdelhadi, 2020). The objective is to propose a contingent conceptual framework to guide future exploratory research and provide a solid theoretical basis for managers and researchers keen to initiate work on Lean Office implementation within Moroccan organizations, thereby contributing to their performance and modernization.